2016
DOI: 10.17511/ijmrr.2016.i10.22
|View full text |Cite
|
Sign up to set email alerts
|

Prescription auditing based on World Health Organization (WHO) prescribing indicators in a teaching hospital in North India

Abstract: Background: Prescription writing is an important means of therapeutic intervention by the doctor and reflects his approach towards safe prescribing. Complacency in prescribing results in errors which can even cause adverse effects. These errors can be detected through a prescription audit. We undertook this study to audit the outpatient department (OPD) prescriptions for completeness of prescription format, legibility and against the World Health Organization (WHO) prescribing indicators recommended to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
43
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 10 publications
5
43
4
Order By: Relevance
“…In this study average number of drugs per prescription was found to be 3.8±1.3 which is similar to what was found by Ahsan et al 8 Other studies have reported a varied range of average number of drugs per prescription from 1.9 to 8.8. 9-13 However it is much higher than the standard value of average number of drugs per prescription (1.6-1.8) set as ideal.…”
Section: Discussionsupporting
confidence: 90%
“…In this study average number of drugs per prescription was found to be 3.8±1.3 which is similar to what was found by Ahsan et al 8 Other studies have reported a varied range of average number of drugs per prescription from 1.9 to 8.8. 9-13 However it is much higher than the standard value of average number of drugs per prescription (1.6-1.8) set as ideal.…”
Section: Discussionsupporting
confidence: 90%
“…These errors make the prescription invalid, as certain drugs can only be dispensed with a valid prescription of the doctor. The prescription errors analyzed by our study were in correlation with errors found in another study done by Ahsan et al where 17% of prescriptions lack the initials of the prescriber [9], leading to serious dosing and dispensing errors. In a study done by Seden et al, it has been suggested that electronic prescribing can eliminate these errors through cautions and alerts at the time of prescribing drugs [14].…”
Section: Discussionsupporting
confidence: 85%
“…The antibiotics prescribed were around 32.22%, which is higher than the designated range by the WHO (≤30%). The percentage of encounters was around 39%, which was comparable to a study done by Ahsan et al [9]. More than one antibiotic is prescribed in 5.12%% of cases.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, lack of knowledge of drug-drug and drug-food interactions can pose a risk of increased adverse effects or even therapeutic failure. 8 Polypharmacy is a major issue seen especially with private practitioners as compared to government doctors, as observed in a study conducted by Ahsan et al 9 This study shows an average of 2.23±1.03 Creating an awareness about the importance of antibiotic stewardship and implementing a rigid hospital antibiotic policy might help in combating the problem of injudicious use of antibiotics leading to antimicrobial resistance. In this study, 25% of prescriptions contained an antibiotic, which is comparable to another study conducted by Chandelkar et al, where 31.8% of prescriptions contained an antibiotic.…”
Section: Discussionmentioning
confidence: 84%